Highly Active Low Cobalt Content-Based Bulk MoS2 Hydrodesulfurization Catalysts with a Unique Impact of H2S - Hamdy Farag; Abd-Alrahman Embaby; Masahiro Kishida; Abdel-Nasser A. El-Hendawy; Mohamed Mahmoud Nasef (Journal of Chemistry)
A series of unsupported MoS2, Co9S8, and Co-promoted MoS2 catalysts have been synthesized by tuned impregnation and successive thermal annealing methods using a continuous flow of a mixture of H2 and H2S gases. The resulting catalysts were evaluated in terms of their activity and selectivity for the hydrodesulfurization of dibenzothiophene (DBT) both in the absence and the presence of H2S. The inclusion of Co onto MoS2 affected both the hydrogenation and direct desulfurization reactions, with the latter (production of biphenyl) being magnified to a much greater degree than the former. Interestingly, low cobalt/molybdenum ratio of ca. 0.05 of the catalyst exhibited outstanding promotion efficiency in the hydrodesulfurization reaction. However, as cobalt is added, the synergy effect drastically decreased. H2S in the reaction mixture led to a remarkable step up in the product from the direct desulfurization reaction route with the most notable increases occurring for the product from the hydrogenation reaction pathway. The HDS activity of such catalysts was much higher than that of the commercial CoMo/Al2O3. The promotion by H2S was discussed.